(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Protein-energy malnutrition and inflammation are common and overlapping conditions in hemodialysis patients, which are associated with increased risk of morbidity and mortality. Adiponectin is an adipocytokine exclusively produced by adipose tissue. The aim of this study was to further elucidate the association between serum adiponectin levels and the nutritional status of hemodialysis patients. Materials and Methods. Seventy-three patients on hemodialysis for at least 3 months, three times weekly, without any acute illness, were divided into 2 groups of well-nourished (n = 25) and malnourished (n = 48) based on their nutritional status, measured by the subjective global assessment. Serum levels of adiponectin, albumin, blood urea nitrogen, and creatinine; body mass index; and the malnutrition-inflammation score were measured in all patients. These values were compared between well-nourished and malnourished patients. The correlations of nutritional variables with serum levels of adiponectin were determined, as well. Results. Except for the malnutrition-inflammation score, which was significantly higher in the malnourished patients compared to the well-nourished ones (11.1 ± 3.6 versus 4.2 ± 2.0, P < .001), no other significant differences were found between the two groups. A weak but significant positive correlation was found between the serum levels of adiponectin and subjective global assessment scores (r = 0.25, P = .03). Conclusions. The results of our study point to potential utility of serum adiponectin level as an indicator of nutritional status in hemodialysis patients. Further studies are needed to clarify the role of adiponectin in the pathogenesis of malnutrition in hemodialysis patients.